Performance of 1, 3‐beta‐D‐glucan in the diagnosis and monitoring of invasive fusariosis. Issue 7 (14th May 2019) - Nucci, Marcio; Barreiros, Gloria; Reis, Henrique; Paixão, Marilene; Akiti, Tiyomi; Nouér, Simone A.
Summary: Invasive fusariosis (IF) usually presents with high fungal burden at diagnosis, and this may contribute to its high mortality rate. The use 1, 3‐beta‐D‐glucan (BDG) may help to establish the diagnosis at an earlier disease stage and to monitor treatment. To evaluate the performance of BDG in the diagnosis of IF and its kinetics in relation to the outcome, we retrospectively tested serum samples of 13 cases of IF, analysed the temporal relationship between the first positive BDG test and the date of the diagnosis of IF, and the kinetics of BDG in relation to patients' outcome. We selected 13 controls with similar underlying diseases as cases, at least two serum samples stored, and no invasive fungal disease. Twelve patients with IF had at least one positive BDG (median 4, range 1‐16). The test was positive before the diagnosis of IF in 11 of the 12 patients (91.6%), at a median of 10 days (range 1‐32). The median BDG value increased (from 109 to 316 pg/mL, P = 0.04) in patients who died by day 30, and did not change significantly (99‐101 pg/mL, P = 0.60) in survivors. Using two consecutive BDG tests, sensitivity, specificity, and positive and negative predictive values were 85%, 69%, 7% and 99%, respectively. BDG is positive in the majority of patients with IF, usually before the diagnosis, but the low positive predictive value limits its use to diagnose IF earlier. Once therapy is started, decreasing BDG values suggests treatment response.